Coleridge's Imagination in " the Rime of Ancient Mariner" - Dr.Ahmad A.Shteywi (مجلة كلية الاداب, 2022)
Coleridge was a poet as well as a philosopher where not we believe in his conviction that "no man was every pact, without being at the same time a profound piles (Biographies Liter aria, II, 19-hereafter BL). In ord understand him as a philosopher, therefore, I think it is to study his philosophy of literature. As a way of understanding his poetic and literary theory I will touch on his concept of imagination defined in chapter 13 of biographies Liter aria, and apply it to one of the supernatural poems "The Rime of the Ancient Mariner" (hereafter "The AM"). Hence the aim of my study is to analyze the poem in connection with his theory of imagination. My main concern is with how imagination works in the poem.